Influence of causatives of germintoses of the digestive tract on biochemical indicators of serum of dogs with mono- and myxed invasions - Kryvoruchenko, D.; Yevstafieva, V. (Scientific Progress & Innovations, 2025)
Biochemical studies of blood serum are important for assessing the functional state of the animal body, which is very often exposed to various types of stress, including parasitic diseases. Helminth invasions are a serious problem for veterinary medicine and public health, since a significant number of parasites have zoonotic potential. As a result of their mechanical, toxic, and trophic action, pathological changes occur not only in the organs and tissues where the helminths are localized, but also in the animal's body as a whole. The aim of the research was to study the peculiarities of the influence of pathogens of helminthiasis of the digestive tract on the biochemical parameters of blood serum of dogs with mono- and mixed invasions. The study was conducted in the conditions of the private veterinary clinic "Dovira" (Kharkiv). Four groups of animals were formed, one of which was a control group (clinically healthy dogs) and three experimental groups (the first group was infested with trichurises, the second group was infested with an association of trichurises and toxocares, and the third group was infested with an association of trichurises, toxocares, and dipylidies). The conducted studies have established the negative impact of helminths on the biochemical parameters of the blood serum of infested dogs. In particular, with trichurous monoinvasion, a slight (P<0.05) increase in the activity of only the enzymes ALT (1.4 times), AST (1.2 times), GGT (1.1 times) and alkaline phosphatase (1.3 times) was detected. With mixed invasions, more significant changes were found in the biochemical parameters of the blood serum of dogs. During trichuric-toxocarosical invasion, an increase in creatinine content (by 20.63 %, P<0.05), total bilirubin (by 15.58 %, P<0.05), enzyme activity (P<0.01) ALT (by 1.5 times), AST (by 1.3 times), GGT (by 1.3 times) and alkaline phosphatase (by 1.3 times), as well as a decrease in glucose content (by 15.52 %, P<0.05) were detected. During trichuric-toxocarosic-dipylidiosical invasion, the blood serum of infected dogs showed greater changes in the content of total protein (P<0.05), albumin (P<0.05), creatinine (P<0.01), total bilirubin (P<0.01), glucose (P<0.01), as well as enzymes (P<0.001) ALT, AST, GGT. The obtained data allow us to take into account the changes that occur in the biochemical parameters of the blood serum of infected dogs with mono- and mixed invasions when prescribing treatment and obtaining a more effective therapeutic effect.